Key Metrics for Evaluating Maritime Supply Chain Performance: Insights from Literature - Hye, Mohammad Nazmuzzaman; Habib, Md. Mamun (International Journal of Supply Chain Management, 2025)
Evaluating performance metrics in maritime supply chain in crucial for achieving operational efficiency, resilience, and service reliability in an increasingly complex global shipping environment. This Study systematically reviews 31 peer-reviewed articles published between 2010 and 2024 to identify, classify, and analyse key performance metrics used in the maritime logistics sector. The review was conducted using four major databases-ScienceDirect, Google Scholar, SpringerLink, and EBSCO Host- following the PRISMA framework. This study employs a systematic literature review (SLR), incorporating thematic analysis to identify and synthesize common patterns across the selected literature. The findings are categorized into three main dimensions: operational efficiency (e.g., berth productivity, vessel on-time performance, ship turnaround time), resilience (e.g., disruption recovery time, supply chain redundancy, routing flexibility), and servicer reliability (e.g., customer satisfaction, delivery accuracy, schedule adherence) The novelty of this paper lies in the development of a comprehensive and structured framework that integrates these key performance metrics, providing maritime stakeholders with actionable insight for performance evaluation and strategic alignment. This farmwork not only synthesizes current academic perspectives but also incorporates digitalization and technological readiness as enablers of enhanced Supply Chain performance. The outcome offers valuable guidance for decision-makers aiming to optimize resource allocation, mitigate risks, and improve overall competitiveness in maritime logistics.